The feasibility study of thermal energy storage application and cogeneration with absorption chillers in a spinning mill - Liu, Bing; Surapong Chiraratananon; Bhattacharya, Sribas C.; Dang, Giap Van; The Government of Japan (Bangkok : Asian Institute of Technology, 1993)
The author would like t o express his sincere gratitude and appreciation to his advisor, Dr. Surapong Chirarattananon, for his expert guidance , suggestion and encouragement throughout this work . Special thanks and appreciation to Dr. Sri bas C. Bhattacharya and Dr. Giap Van Dang for their valuable suggestions , advice and kind serving as members of his examination committee. The author is grateful to the Government of Japan who provided scholarship and financial support for his study. The author is highly obliged and thankful to Mr . Yang Yanru, chief representative of China National General Machinery Enginering Corporation in Thailand, Mr. Yu Jiancang, manager of chi nese expert team in Thai Melon Textile Co. , Ltd. , (TMT) for provi di ng necessary guidance and helping in data and information collecti on. The author is equally indebted to Asian Institute of Technology f or providing him opportunity of postgraduate study , faculties , staff members of the Energy Technology Division, all his friends , who directly and indirectly help for the research as well as his study at AIT. Finally, no word can express the author's deepest gratitude and appreciation to his parents and other family members, especially to his wife and daughter, for their continuous encouragement and love throughout his career . This work i s dedicated to his family.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
The thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Cogeneration of electric power and heat